1994
DOI: 10.1159/000100323
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Linear Radiosurgery for Cavernous Angiomas

Abstract: Optimal management of symptomatic cavernous angiomas (CA) located in the thalamus and the brainstem is problematic. Clinical and radiological (MRI) follow-up series suggest that having hemorrhaged once, recurrent hemorrhage with progressive neurologic dysfunction may commonly occur. We have therefore chosen to treat these lesions when first symptomatic with stereotactic linear radiosurgery (SLR). We now report, after a median follow-up of 27 months, 12 patients with CAs (9 women, 3 men, mean age 40 years) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Thus far, only a few authors provided outcome data of patients treated with LINAC radiosurgery. Although the number of observed patients was significantly smaller, similar reductions of the annual hemorrhage rate were documented [36,46,47,48]. With an annual hemorrhage rate of 12.5% within the first 2 years after radiosurgery and 4.8% overall, our observations confirm these results.…”
Section: Discussionsupporting
confidence: 87%
“…Thus far, only a few authors provided outcome data of patients treated with LINAC radiosurgery. Although the number of observed patients was significantly smaller, similar reductions of the annual hemorrhage rate were documented [36,46,47,48]. With an annual hemorrhage rate of 12.5% within the first 2 years after radiosurgery and 4.8% overall, our observations confirm these results.…”
Section: Discussionsupporting
confidence: 87%
“…This policy seemed to us logical especially when considering that CMs treated conservatively generally lead to severe disability and entail a mortality rate of the order of 20% [35]. The radiosurgical option, in spite of some articles claiming that radiosurgery might be e¨ective in CMs [13,28], did not prove to be e½cacious or even innocuous [2,11,26,29].…”
Section: Results Of Surgerymentioning
confidence: 99%
“…Nearly 10-fold decreases in overall bleed rates were reported in the studies of Kim et al 26 and Tsien et al 61 On the other hand, postradiosurgery clinical event rates only decreased from 2.0 to 1.6% in the study of Liscák et al, 35 and data provided by Stea et al 57 did not demonstrate a significant decrease in hemorrhage rates.…”
Section: Hemorrhage Ratesmentioning
confidence: 86%
“…24,35,44,46,57 Authors reported overall postradiosurgical hemorrhage rates ranging from 1.6 to 8%. This higher range may reflect insufficient follow-up as in the Kim et al…”
Section: Discussionmentioning
confidence: 99%